PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 016 TANAH DATAR - Ziaulhaq '; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research based on the promlems that was discovered when the learning IPA in class V SDN 016 Tanah Datar that shows the results of learning IPA is still low. The formula the problem in this study is : “Whether the implementation of the Learning Contextual Teaching and Learning (CTL) can improve results learn IPA students of class V SDN 016 Tanah Datar.” The purpose of this research is to improve results learn IPA students of class V SDN 016 Tanah Datar by applying an approach Contextual Teaching and Learning (CTL). The hypothesis in this study is, “ If applied approach Learning Contextual Teaching and Learning (CTL) than can improve results learn IPA students of class V SDN 016 Tanah Datar 0n April 2016. This research is  research action class (PTK) with two cycle. The subject of this research is students of class V SDN 016 Tanah Datar in 2015/2016 years lesson consist of 18 students with 9 the male and 9 people female. The results of research shows increasing skill teachers in the meeting I get the scores 15 with the percentase 62,50 in good category, the meeting II scores 17 with the percentase 70,83 in good category, a quarter  scores 18 with the percentase 75,00 in good category, the meeting IV scores 20 with the percentase 83,33 invery good category. The activity of students have increased with acquisition scores at the meeting I of 15 whit the percentase 62,50 in good category, the meeting II scores 16 with the percentase 66,67 in good category,  a quarter  scores 17 whit the percentase 70,83 in good category, the meeting IV scores 18 whit the percentase 75,00 in good category. The results of learning IPA also experienced by the persentase increase thoroughly learn cycle I of 77,78%, cycle II of 94,44%. Thus it can be concluded that implentations of the Learning Contextual Teaching and learning (CTL) can improve results learn IPA students of class V SD NEGERI 016 Tanah Datar.    Key words : Approach CTL, Improve results learn IPA.